2023
DOI: 10.1186/s12889-023-16338-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between systemic immune-inflammation index and low muscle mass in US adults: a cross-sectional study

Abstract: Background Chronic inflammatory responses have been reported to be associated with low muscle mass and systemic immune-inflammation index(SII) is a novel indicator of inflammation. The purpose of our study was to clarify the relationship between SII and low muscle mass. Methods This study was a cross-sectional study based on National Health and Nutrition Examination Survey (2011–2018). SII was calculated as the platelet count × neutrophil count/lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…According to previous literature, the relationship between physical activity and sarcopenia may be related to inflammation. Inflammation is a well-known factor contributing to sarcopenia progression 34 36 . In exercised muscle, inflammatory cytokines such as IL-6 recruit immune cells and produce IL-10 receptor antagonists decreasing inflammatory injury 37 .…”
Section: Discussionmentioning
confidence: 99%
“…According to previous literature, the relationship between physical activity and sarcopenia may be related to inflammation. Inflammation is a well-known factor contributing to sarcopenia progression 34 36 . In exercised muscle, inflammatory cytokines such as IL-6 recruit immune cells and produce IL-10 receptor antagonists decreasing inflammatory injury 37 .…”
Section: Discussionmentioning
confidence: 99%
“… 35 Studies have also indicated that higher values of PLR, NLR, SII, and SIRI, and lower LMR values are closely associated with higher prevalence of sarcopenia in populations aged 50 or older in China, as well as an increased SII value in a large population aged 20 years and over is associated with a higher risk of low muscle mass in the United States. 17 , 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…The systemic immune-inflammatory index (SII) was initially described as a potential marker for tumor and cardiovascular disease. [ 10 12 ] It is calculated as the platelet count multiplied by the neutrophil count and then divided by the lymphocyte count. [ 13 , 14 ] SII has been recognized as a better indicator of inflammation status.…”
Section: Introductionmentioning
confidence: 99%